2019
DOI: 10.4314/sajas.v49i3.19
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia levels on <i>in vitro</i> degradation of fibrous carbohydrates from buffel grass

Abstract: This study was carried out to examine the degradation dynamics of neutral detergent fibre (NDF) and the profile of volatile fatty acids that originate from the fermentation of buffel grass (Cenchrus ciliaris, L.) with various levels of ammonia in the growth medium. The treatments consisted of six levels of ammonia in the growth medium (0, 5, 10, 15, 20 and 30 mg/dL), which were obtained by adding urea. These in vitro incubation times were evaluated in three replicates per time for 0, 3, 6, 9, 12, 24, 36, 48, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…The increase in the ammoniacal nitrogen (N-NH 3 ) provided by NPN infusion corroborates a previous in vitro study which showed a linear increase of N-NH 3 in a medium containing buffel grass and different concentrations of nitrogen ammonia (Santana Neto et al, 2019). Interestingly, no changes in other ruminal parameters were observed in our study (pH, acetate, propionate, butyrate and total VFA).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The increase in the ammoniacal nitrogen (N-NH 3 ) provided by NPN infusion corroborates a previous in vitro study which showed a linear increase of N-NH 3 in a medium containing buffel grass and different concentrations of nitrogen ammonia (Santana Neto et al, 2019). Interestingly, no changes in other ruminal parameters were observed in our study (pH, acetate, propionate, butyrate and total VFA).…”
Section: Discussionsupporting
confidence: 92%
“…Pires et al (2016) reported a 20% increase in the NDF degradation rate at 15 mg/dl N-NH 3 in the rumen fluid, compared to the treatment without N-NH 3 . Santana et al (2019) also observed that an N-NH 3 concentration of 17.76 mg/dl maximized NDF degradation from buffel grass by goat rumen microorganisms.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Previous studies, such as McDonald et al [49] , have illustrated that the concentration of NH 3 –N in ruminal fluid typically ranges from 8.5 to 30 mg/100 ml. However, it is worth noting that excess NH 3 –N exceeding 50 mg NH 3 –N/l does not significantly impact microbial protein synthesis and is ultimately excreted, as indicated by Neto et al [50] .…”
Section: Discussionmentioning
confidence: 92%